Nanoscale Assembly of Paramagnetic Organic Radicals on Au(111) Single Crystals. Issue 10 (25th January 2013) - Savu, Sabine‐Antonia; Biswas, Indro; Sorace, Lorenzo; Mannini, Matteo; Rovai, Donella; Caneschi, Andrea; Chassé, Thomas; Casu, Maria Benedetta
Abstract: The successful thin‐film deposition of a pyrene‐substituted nitronyl nitroxide radical under controlled conditions has been demonstrated. The electronic properties, chemical environment at the interface, and morphology of the thin films have been investigated by a multitechnique approach. Spectroscopic and morphological analyses indicate a Stranski–Krastanov growth mode and weak physisorption of molecules onto the metallic surface. Electron spin resonance (ESR) spectroscopy shows that evaporation processes and deposition do not affect the paramagnetic character of the molecules. Useful concepts for the engineering of new, purely organic‐based magnets, which may open the way to fruitful exploitation of organic molecular‐beam deposition for assembly on solid surfaces in view of future technological applications, are presented. Abstract : Radical magnets : One of the main challenges in organic magnetism is the deposition and growth of highly oriented layers down to the sub‐monolayer regime on a substrate. The controlled deposition of a pyrene‐substituted nitronyl nitroxide radical on an Au(111) surface was investigated (see figure). The interface between the organic radical and metal surface and the surface and magnetic properties of the assemblies have been investigated, addressing important issues for future technological applications.